The opportunities of countering corruption offenses through the use of blockchain technology - Tokatov, R.A.; Bazarov, M.M.; Alimkulova, B.K. (Bulletin of the Karaganda University “Law Series”, 2023)
The purpose of the study is to consider the possibilities of blockchain technology to prevent corruption offenses. The research uses fundamental and applied, legal comparisons, legal statistical, system, logical, functional methods of scientific research. Achieved results. The potential of blockchain technology is provided in the prevention of corruption offenses. Priorities and vulnerabilities of the technological system are revealed. Foreign experience was studied, the basics of the legislation of Kazakhstan for the introduction of technology were studied. A brief summary. Blockchain technology makes it possible to prevent corruption offenses by eliminating the circumstances that give rise to them. As a result of the study, the legal basis for the introduction of this information and communication technology into Kazakhstani legislation was determined. The formation of financial and accounting documents in the blockchain information system in the field of public and quasipublic procurement, where corruption offenses are widespread, can become an effective means of deterring theft of budget funds and fraud in this area. Consideration of blockchain technology as a means of preventing corruption offenses and preparation for further legal research in this direction is the scientific significance of the study. The practical significance of the study will be to increase the effectiveness of the measures taken to combat corruption, help reduce the level of corruption offenses and, as a result, create the foundations for socio-economic development. The results of the research can be used in the field of combating corruption, public and quasi-public procurement, public services.